47 Disability weights from the injury vibes collaboration. (1st September 2016) - Lyons, Ronan A; Gabbe, Belinda J; Simpson, Pam M; Harrison, James E; Ameratunga, Shanthi; Derrett, Sarah; Polinder, Suzanne; Rivara, Frederick P
Abstract : Background: Disability weights (DWs) are an integral part of deriving the years lived with disability (YLD) component of disability adjusted life years (DALYs). DWs can be derived through different methods including panels comprising of experts, the general population judging the impact of conditions on loss of health, or through follow-up data on the health-related quality of life of groups of injured patients. The Validating and Improving injury Burden Estimates Study (Injury-VIBES) sought to create new injury DWs by combining data from six of the largest injury outcome studies, that were conducted in Australia, New Zealand, United Kingdom, Netherlands and USA. Methods: Data were combined in an individual level meta-analysis from the Victorian State Trauma Registry, Victorian Orthopaedic Trauma Outcomes Registry, Dutch Injury Patient Survey, UK Burden of Injury Study, Prospective Outcomes of Injury Study, and the National Study on Costs and Outcomes of Trauma. DWs were calculated for individual and grouped ICD10 diagnosis codes and established nature of injury classifications. Twelve month annualised DWs (assumed to be indicative of permanent health loss) were calculated separately for cases discharged following treatment in an emergency department or as a hospital admission. Results: There were 29, 770 injury cases aged ≥ 18 years included in the analysis. Results will be provided by individal and grouped ICD10 codes and the GBD 2013 and EU Injury Data Base categorisations. For most injury groups DWs revealed greater health loss than previously published estimates and differ from those used in the GBD project. There were marked differences in DWs for cases hospitalised vs those not. Conclusions: Injury VIBES has produced sets of empirically derived DWs that will useful to the injury research community in measuring the population burden of injury.